Significant Other’s Anticipated Emotions Increase Student’s Intention to Avoid Smoking - Simamora, Bilson (Bina Nusantara University, 2021)
The research started with a premise that individuals could take the initiative and regulate their behavior to generate Significant Others’ Anticipated Emotions (SOAEs). Could the SOAEs function as a social element of behavior in addition to subjective norms (SN)? The research aimed to answer this question. Therefore, the researcher extended the Theory of Planned Behavior (TPB) and argued that the SOAEs influenced behavioral intention through attitude toward behavior based on cognitive balance theory. In the smoking abstinence behavioral context, the researcher tested the extended model. The data from 242 respondents chosen conveniently, analyzed using structural equation modeling, revealed that Significant Others’ Anticipated Joyfulness (SOAJ) for smoking abstinence behavior and Significant Others’ Anticipated Distress (SOAD) for smoking behavior positively influences anti-smoking behavior through attitude. Moreover, the sole influence of the SOAJ and cumulative influence of SOAJ and SOAD on smoking abstinence intention are higher than that of the SN. As a new component of TPB, the SOAEs complement and do not rival the SN. Other researchers can utilize a longitudinal research design and test the extended model in different contexts of behaviors.